Stability Analysis of Mine Drift for Explosive Welding - Jang, Hyong Doo; Yang, H.; Jang, M. (Korean Society of Explosives and Blasting Engineering, 2010)
Explosive welding was planed in a closed drift of a mine for its reuse. In this study, we analyzed the stabilization of roof and pillar which were expected to be affected by overpressure experienced during the continual explosive welding. Three equations, normal equation, CONWEP and DDESB, were used for the estimation of overpressure. The investigation shows that the continual use of the explosive welding in a drift may result in considerable damage on the drift.